Performance on Partial Replacement of Fine Aggregate with Marble Dust Powder (International Journal of Innovative Research in Computer Science & Technology, 2022)
The construction buildings which are present  in and around coastal area are severely facing lot of  problems. This is due to penetration of sea salts. This leads  to damage of structure fast. The average NACL  Concentration of sea water is about3.5%. In this study ,  Marble Dust powder as been taken to analyze the chemical  and physical properties of the concrete which is partial  replaced with marble dust powder as fine aggregate by  10%,20%,30%,40% and 50%by weight of fine Aggregate.  After replacing this marble dust powder as fine aggregate,  cylinders and cubes are casted. After casting this cubes and  cylinders, they are using to know its both compressive as  well as tensile strength by using compression test and split  tensile strength for 7 days and 28 days.
Keywords: Water Cement ratio; Cement Content; Gradation of the Aggregate; Consistency; marble dust